PRAGMATICS: WHY USE AUDIOVISUAL INPUT IN SECOND AND FOREIGN LANGUAGE LEARNING CONTEXTS? - Rodríguez-Peñarroja, Manuel (Revista Docência e Cibercultura, 2020)
The teaching and acquisition of pragmatics in second and foreign language learning contexts has been traditionally reduced to coursebooks’ decontextualized dialogue samples and static images with almost no effects on learners’ communicative competence. This paper outlines rationale on the teaching of pragmatics since it has become of essential importance as specified in different language proficiency paradigms i.e. the CEFR. Thus, attention is centered on the use of audiovisual materials as a rich input source used for that aim. With this in mind, a review of studies appraising for the validity of language used in audiovisual genres is provided. In addition, an overview of its applicability and effects as a part of the general education curricula and in second and foreign language instruction is presented. Results from the studies reviewed reported overall advantageous outcomes when using this type of input for different instructional aims and more specifically with pragmatics’ acquisition purposes.